DARK ANGEL - Sandford, John, 1944 February 23- (New York : G. P. Putnam's Sons, 2023)
"Letty Davenport, the tough-as-nails adopted daughter of Lucas Davenport, takes on an undercover assignment that brings her across the country and into the crosshairs of a dangerous group of hackers"--
NOT YET PUBLISHED : DUE APRIL 11, 2023.
Keywords: Davenport, Letty -- (Fictitious character) -- Fiction; Davenport, Lucas -- (Fictitious character) -- Fiction; Criminal investigation -- Fiction; California -- Fiction; Detective and mystery fiction; Thrillers (Fiction)